Policy reform in Israel: Perceptions of Arab Palestinian kindergarten teachers - Kussai Haj-Yehia; Marwa Sarsor; Hiba Amara (Journal of Childhood, Education & Society)
The research investigated the perceptions of kindergarten teachers in Arab Palestinian society concerning the contribution of the latest Israeli government education reform entitled the "New Horizons" reform to provide additional material enabling assessment of the reform's efficacy and attainment of its goals in Arab Palestinian kindergartens. Previous studies have shown inconsistent results concerning the benefits of the reform and indicated that educators had both positive and negative views concerning its different elements. A qualitative research study gathered data from semi-structured interviews with 16 Arab Palestinian kindergarten teachers. The findings indicated that the teachers were dissatisfied with the reform, indicating different negative aspects of the reform: burdensome work, intensive work, and lack of autonomy for the teachers, unsuitability of the programs for the kindergarten's workday and its structure. Although teachers indicated that the reform had a positive influence on the children's achievements and their progress, it also generated pressure on the teachers. The research findings clarify the way in which the reform is seen by these Arab Palestinian kindergarten teachers and points to the need for further studies, which will investigate kindergarten teachers' work in the local and global context.